2014
DOI: 10.1109/tbme.2014.2315784
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Prior-to-Impact Fall Event Detection Algorithm

Abstract: Automatic fall event detection has attracted research attention recently for its potential application in fall alarming system and wearable fall injury prevention system. Nevertheless, existing fall detection research is facing various limitations. The current study aimed to develop and validate a new fall detection algorithm using 2-D information (i.e., trunk angular velocity and trunk angle). Ten healthy elderly were involved in a laboratory study. Sagittal trunk angular kinematics was measured using inertia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Similarly, Tong et al [11], Aberyuwan et al [12], and Pannurat et al [13] used machine learning technologies to analyze signals that were received from triaxial accelerometers that were distributed over a body. In addition, Liu et al [14] detected falls by using not only acceleration information but also angular velocity information. The accuracy of wearable-device-based methods can be improved by obtaining Appl.…”
Section: Wearable-device-based Methodsmentioning
confidence: 99%
“…Similarly, Tong et al [11], Aberyuwan et al [12], and Pannurat et al [13] used machine learning technologies to analyze signals that were received from triaxial accelerometers that were distributed over a body. In addition, Liu et al [14] detected falls by using not only acceleration information but also angular velocity information. The accuracy of wearable-device-based methods can be improved by obtaining Appl.…”
Section: Wearable-device-based Methodsmentioning
confidence: 99%
“…Data from wearable IMUs was used as the input of this function to search the optimal thresholds that can distinguish falls from activities of daily living (ADLs). The evaluation results showed that the fall detection performance was enhanced with such an integrative system [ 22 ].…”
Section: Fall Detection Apparatusmentioning
confidence: 99%
“…Head acceleration [ 13 , 21 ] and upper arm velocity [ 13 ] were also used to define fall detection indicators. Fall detection indicators defined by rotational measures included angular rate of the sternum [ 33 ], angular rate of the waist [ 32 , 41 , 43 ] and trunk [ 22 , 23 ], and segment orientation of the trunk [ 22 , 23 ] and thigh [ 31 , 32 ]. Most existing studies used a single kinematic measure to define the fall detection indicator.…”
Section: Fall Detection Indictorsmentioning
confidence: 99%
See 2 more Smart Citations